2016
DOI: 10.1016/j.scitotenv.2015.09.133
|View full text |Cite
|
Sign up to set email alerts
|

Fine and ultrafine particulate organic carbon in the Los Angeles basin: Trends in sources and composition

Abstract: In this study, PM2.5 and PM0.18 (particles with dp < 2.5μm and dp < 0.18μm, respectively) were collected during 2012-2013 in Central Los Angeles (LA) and 2013-2014 in Anaheim. Samples were chemically analyzed for carbonaceous species (elemental and organic carbon) and individual organic compounds. Concentrations of organic compounds were reported and compared with many previous studies in Central LA to quantify the impact of emissions control measurements that have been implemented for vehicular emissions over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 92 publications
5
31
1
2
Order By: Relevance
“…Furthermore, with considerably greater resources than the present study, the previous study measured air pollutants at the residential location (retirement communities) of each subject group that likely greatly reduced exposure error. Another possible explanation for why our current results for the systemic biomarkers are not as definitive as our previous studies could be due to the fact that the air pollutant levels, especially ultrafine PM, EC, OC, and tracers of mobile sources measured by our research group, have decreased over the last decade in the Los Angeles area (Shirmohammadi et al 2016). This resulted from more stringent regulations on mobile source emissions by the United States EPA, California Air Resources Board and SCAQMD (Hasheminassab et al 2014a).…”
Section: Discussioncontrasting
confidence: 83%
“…Furthermore, with considerably greater resources than the present study, the previous study measured air pollutants at the residential location (retirement communities) of each subject group that likely greatly reduced exposure error. Another possible explanation for why our current results for the systemic biomarkers are not as definitive as our previous studies could be due to the fact that the air pollutant levels, especially ultrafine PM, EC, OC, and tracers of mobile sources measured by our research group, have decreased over the last decade in the Los Angeles area (Shirmohammadi et al 2016). This resulted from more stringent regulations on mobile source emissions by the United States EPA, California Air Resources Board and SCAQMD (Hasheminassab et al 2014a).…”
Section: Discussioncontrasting
confidence: 83%
“…The contribution of secondary ions to PM 2.5 mass concentration was 33 and 31% in Central LA and Anaheim, respectively, while in the PM 0.18 size fraction they accounted for 13 and 14% in Central LA and Anaheim, respectively. More details on aerosol chemical composition and mass concentrations are discussed elsewhere 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The results discussed in the previous section revealed that vehicular abrasion, an important component of non-tailpipe emissions, together with secondary OC, were two major sources significantly contributing to PM 2.5 DTT activity, in addition to tailpipe emissions. Shirmohammadi et al 31 recently showed that important tracers of tailpipe emissions in PM 2.5 and PM 0.18 such as PAHs, hopanes and steranes concentrations have decreased by 40–70% and 50–70%, respectively over the past decade in Central LA. These findings, along with the comparison of ultrafine PM redox activity with previous studies, corroborate the effectiveness of stringent regulations on vehicular tailpipe emissions in reducing the overall ambient ultrafine PM toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been found in other studies our results indicate that main sources of the finest PM components are linked with combustion processes. In fact, major sources of fine particles in urban areas are vehicular emissions especially of diesel vehicles (Shirmohammadi et al, 2016). In our case, however biomass combustion also seems to have a considerable contribution in PM 2.5 and PM 1 levels what could be related to the plant activity.…”
Section: Sources Of Organic Pmmentioning
confidence: 46%